ON THE COMPARATIVE EFFICIENCY OF TRAWLS MADE OF COTTON POLYETHYLENE AND COMBINATION OF BOTH THE MATERIALS. - KARTHA, R N; GEORGE, V C; RADHALAKSHMI, K (Fishery Technology, 2017)
The merits and demerits of cotton, polyethylene and combination of the two materials ascertained on the basis of cost, wear and tear, maintenance, total catch and qualitative analy is of the catch are discussed by making comparative fishing experiments with the three trawl gears made of these materials. The study can be concluded with a suggestion for switching over to polyethylene twisted monofilarnents for better, in case of bottom trawls without in any way adversely affecting the catch of shrimps and at the same time for enhanced fish catch. Eventhough the combination net is found to be equal in efficiency as the polyethylene net this idea cannot be conveniently adopted from the point of view of economy.